ANALISYS OF DUST LEVELS AND MASKS USAGE BEHAVIOR ON RESPIRATORY DISORDER COMPLAINTS OF RICE MILLING WORKERS - Rahma, Ratih Andhika Akbar; Afif A, Dian; Bintoro A, Elnanda (Journal of Vocational Health Studies, 2018)
Background: The Impementation of occupational safety and health at home industry in Ponorogo is not yet optimal, one of them is rice milling industry which produces rice dust during the production process. Dust levels that exceeds the threshold limit value may cause respiratory disoder complaints. The use of masks that conform with standard is one of way to reduce dust exposure to workers. Purpose:  To analyze the dust level and masks usage behavior on respiratory disorder complaints of rice milling workers in Gegeran Village, Sukorejo, Ponorogo. Method: This research used the observational analytical method with the cross-sectional design. Its population was 23 workers. The samples of research were taken by using the total sampling technique. Measurement of dust level used high volume sampler. Measurement of masks usage behavior and respiratory disorder complaints used questionnaire.  Data analysis used Lambda test in SPSS program version 24. Result: Dust levels of rice milling indoor and outdoor exceeds the threshold limit values, each of them is 598,3 mg/m3 and 11,08 mg/m3. Score of use mask behavior is 72,5%. Rice milling workers that have respiratory disorder complaints is 19 workers (83%). The result of Lambda test shows that there is no significant correlation between dust levels and masks usage behavior with respiratory disorder complaints. Conclusion: Dust levels and masks usage behavior has no significant correlation to respiratory disorder complaints of rice milling workers in Gegeran Village, Sukorejo, Ponorogo.